2005
DOI: 10.1073/pnas.0506893102
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-donating aspirin induces apoptosis in human colon cancer cells through induction of oxidative stress

Abstract: Nitric oxide-donating aspirin (NO-ASA) is a promising chemoprevention agent against colon cancer and other cancers. It consists of traditional ASA to which a NO-releasing moiety is bound through a spacer. NO-ASA inhibits colon cancer cell growth several hundred times more potently than does ASA. In Min mice, NO-ASA inhibited intestinal carcinogenesis without affecting cell proliferation. Thus, we examined whether NO-ASA's most important cell kinetic effect is the induction of apoptosis. After confirming induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 25 publications
7
103
0
Order By: Relevance
“…NO release triggered the production of reactive radicals and, as a consequence, led to reduction of cell viability that was further verified by the antioxidant-N-acetylcysteine treatment. This is consistent with the ability of NO-donating aspirin to induce apoptosis in human colon cancer cells through induction of oxidative stress (10). However, it was recently shown that antitumor property of NO-NSAIDs was not the consequence of attached NO but could be ascribed to the NO carrier (40).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…NO release triggered the production of reactive radicals and, as a consequence, led to reduction of cell viability that was further verified by the antioxidant-N-acetylcysteine treatment. This is consistent with the ability of NO-donating aspirin to induce apoptosis in human colon cancer cells through induction of oxidative stress (10). However, it was recently shown that antitumor property of NO-NSAIDs was not the consequence of attached NO but could be ascribed to the NO carrier (40).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, it was shown that NOaspirin was capable to induce apoptosis in colon cancer cells, whereas the other drug, NO-sulindac, was responsible for apoptotic death of bladder and prostate carcinoma (9,10). Several evidences indicate that the capacity of the tumor cells to develop resistance to pharmacologically induced apoptosis plays a key role in determining their resistance to chemotherapy (32).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the population of Annexin V þ and PI þ cells was observed at higher dose of QCA. It is well known that ROS production and apoptosis are closely related and activation of caspase-3 is one of hallmark consequences of GSH depletion 35,36 . Therefore, the superior apoptosis-inducing potential of QCA is attributed to the combined effects of GSH-depleting QM and ROS-generating cinnamaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are also studies suggesting the protective role of NO such as reduction of tumor cell adhesion to endothelium (Kong et al, 1996) increasing the blood flow (Dhar et al, 2003) and modulation of apoptosis. (Choi et al, 2002;Fabbri et al, 2005;Gao et al, 2005;Lu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%